Join TSR now and get all your revision questions answeredSign up now
    • Thread Starter
    Offline

    14
    ReputationRep:
    a) x^1/2 + 2x^-1/2 = 3

    b) x + x^1/2 = 12

    I know the answers because I did trial and error in my head. If I am do to lines of working out, what steps lead to the answer?
    • Community Assistant
    • Welcome Squad
    Offline

    17
    ReputationRep:
    (Original post by Baaah)
    a) x^1/2 + 2x^-1/2 = 3

    b) x + x^1/2 = 12

    I know the answers because I did trial and error in my head. If I am do to lines of working out, what steps lead to the answer?
    Let A=x^{1/2}

    Your part a turns into A+2A^{-1}=3 then multiply through by A and solve the quadratic in A. Then once you have A=... turn it into x^{1/2}=... and get x.

    Same with part b. It would turn into A^2+A=12
    Offline

    2
    ReputationRep:
    (Original post by Baaah)
    a) x^1/2 + 2x^-1/2 = 3

    b) x + x^1/2 = 12

    I know the answers because I did trial and error in my head. If I am do to lines of working out, what steps lead to the answer?
    a) To solve x^1/2 + 2x^-1/2 = 3

    let Y = x^(1/2)

    remember 2x^(-1/2) = 2/x^(1/2)

    ; Y + 2/Y = 3

    *Y ; Y^2 + 2 = 3Y

    ; Y^2 - 3Y + 2 =0

    ; (Y - 1)(Y - 2) = 0

    ; Y = 1 , Y = 2

    Substitute Y = 1 and Y = 2 into Y = x^(1/2)

    ; 1 = x^(1/2) ; 2 = x^(1/2)

    ; x = 1 ; x = 4

    b) To solve x + x^1/2 = 12

    let U = x^1/2

    remember x = (x^1/2)^2

    therefore ; U^2 + U = 12

    ; U^2 + U - 12 = 0

    ; (U + 4)(U - 3)

    ; U = -4 , U = 3

    substitute U = -4 and U = 3 into U = x^1/2

    ; -4 = x^1/2 ; 3 = x^1/2

    ; x = no solution ; x = 9


    Hope this helps
    • Community Assistant
    • Welcome Squad
    Offline

    17
    ReputationRep:
    (Original post by Pixel Warrior)
    a) To solve x^1/2 + 2x^-1/2 = 3

    let Y = x^(1/2)

    remember 2x^(-1/2) = 2/x^(1/2)

    ; Y + 2/Y = 3

    *Y ; Y^2 + 2 = 3Y

    ; Y^2 - 3Y + 2 =0

    ; (Y - 1)(Y - 2) = 0

    ; Y = 1 , Y = 2

    Substitute Y = 1 and Y = 2 into Y = x^(1/2)

    ; 1 = x^(1/2) ; 2 = x^(1/2)

    ; x = 1 ; x = 4

    b) To solve x + x^1/2 = 12

    let U = x^1/2

    remember x = (x^1/2)^2

    therefore ; U^2 + U = 12

    ; U^2 + U - 12 = 0

    ; (U + 4)(U - 3)

    ; U = -4 , U = 3

    substitute U = -4 and U = 3 into U = x^1/2

    ; -4 = x^1/2 ; 3 = x^1/2

    ; x = no solution ; x = 9


    Hope this helps
    Damn, can I get you to do my homework for me as well???
    • Thread Starter
    Offline

    14
    ReputationRep:
    (Original post by Pixel Warrior)
    a) To solve x^1/2 + 2x^-1/2 = 3

    let Y = x^(1/2)

    remember 2x^(-1/2) = 2/x^(1/2)

    ; Y + 2/Y = 3

    *Y ; Y^2 + 2 = 3Y

    ; Y^2 - 3Y + 2 =0

    ; (Y - 1)(Y - 2) = 0

    ; Y = 1 , Y = 2

    Substitute Y = 1 and Y = 2 into Y = x^(1/2)

    ; 1 = x^(1/2) ; 2 = x^(1/2)

    ; x = 1 ; x = 4

    b) To solve x + x^1/2 = 12

    let U = x^1/2

    remember x = (x^1/2)^2

    therefore ; U^2 + U = 12

    ; U^2 + U - 12 = 0

    ; (U + 4)(U - 3)

    ; U = -4 , U = 3

    substitute U = -4 and U = 3 into U = x^1/2

    ; -4 = x^1/2 ; 3 = x^1/2

    ; x = no solution ; x = 9


    Hope this helps
    2x^(-1/2) = 2/x^(1/2)
    I thought 2x^(-1/2) = 1/2x^(1/2) ?
    Offline

    14
    ReputationRep:
    nope
    (Original post by Baaah)
    2x^(-1/2) = 2/x^(1/2)
    I thought 2x^(-1/2) = 1/2x^(1/2) ?
    Offline

    2
    ReputationRep:
    (Original post by Baaah)
    2x^(-1/2) = 2/x^(1/2)
    I thought 2x^(-1/2) = 1/2x^(1/2) ?
    No that's wrong

    by breaking it up you see that

    2x^(-1/2) = 2 * x^(-1/2)

    = 2 * 1/x^(1/2)

    = 2/x^(1/2)
    • Thread Starter
    Offline

    14
    ReputationRep:
    (Original post by Pixel Warrior)
    No that's wrong

    by breaking it up you see that

    2x^(-1/2) = 2 * x^(-1/2)

    = 2 * 1/x^(1/2)

    = 2/x^(1/2)
    Oh I see

    I was confused because I thought a negative index meant I just have to make the whole base a reciprocal
    Offline

    13
    ReputationRep:
    (Original post by Baaah)
    2x^(-1/2) = 2/x^(1/2)
    I thought 2x^(-1/2) = 1/2x^(1/2) ?
    2x^{\frac{-1}{2}} = 2 \times x^{\frac{-1}{2}} = 2 \times \dfrac{1}{x^{\frac{1}{2}}} = \dfrac{2}{x^{\frac{1}{2}}}

    Ahh, beaten to it. Never mind...
    • Thread Starter
    Offline

    14
    ReputationRep:
    (Original post by K-Man_PhysCheM)
    2x^{-1/2} = 2 \times x^{-1/2} = 2 \times \dfrac{1}{x^{1/2}} = \dfrac{2}{x^{1/2}}

    Ahh, beaten to it. Never mind...
    Well thanks anyway

    No wonder I kept getting it wrong...
    • Thread Starter
    Offline

    14
    ReputationRep:
    (Original post by Pixel Warrior)
    a) To solve x^1/2 + 2x^-1/2 = 3

    let Y = x^(1/2)

    remember 2x^(-1/2) = 2/x^(1/2)

    ; Y + 2/Y = 3

    *Y ; Y^2 + 2 = 3Y

    ; Y^2 - 3Y + 2 =0

    ; (Y - 1)(Y - 2) = 0

    ; Y = 1 , Y = 2

    Substitute Y = 1 and Y = 2 into Y = x^(1/2)

    ; 1 = x^(1/2) ; 2 = x^(1/2)

    ; x = 1 ; x = 4

    b) To solve x + x^1/2 = 12

    let U = x^1/2

    remember x = (x^1/2)^2

    therefore ; U^2 + U = 12

    ; U^2 + U - 12 = 0

    ; (U + 4)(U - 3)

    ; U = -4 , U = 3

    substitute U = -4 and U = 3 into U = x^1/2

    ; -4 = x^1/2 ; 3 = x^1/2

    ; x = no solution ; x = 9


    Hope this helps
    Sorry to bother you again

    -4 = x^1/2
    Wouldn't that mean x has a solution of 16 because (-4)^2 = 16? Why is there no solution :?
    Offline

    2
    ReputationRep:
    (Original post by Baaah)
    Sorry to bother you again

    -4 = x^1/2
    Wouldn't that mean x has a solution of 16 because (-4)^2 = 16? Why is there no solution :?
    I guess that since sqrt(16) gives +/- 4 you are correct, but you should ask a teacher or something as its been a while since i've done this.

    And no probs, happy to help
    • Community Assistant
    • Welcome Squad
    Offline

    17
    ReputationRep:
    (Original post by Baaah)
    Sorry to bother you again

    -4 = x^1/2
    Wouldn't that mean x has a solution of 16 because (-4)^2 = 16? Why is there no solution :?
    No because \sqrt{x} is always greater than or equal to 0.

    Besides, 16+4\not= 12 when you plug it back through the equation.
    • Community Assistant
    • Welcome Squad
    Offline

    17
    ReputationRep:
    (Original post by Pixel Warrior)
    I guess that since sqrt(16) gives +/- 4 you are correct, but you should ask a teacher or something as its been a while since i've done this.

    And no probs, happy to help
    \sqrt{16} \not= \pm 4

    \Rightarrow \sqrt{16}=4
 
 
 
Poll
Which web browser do you use?
Help with your A-levels

All the essentials

The adventure begins mug

Student life: what to expect

What it's really like going to uni

Rosette

Essay expert

Learn to write like a pro with our ultimate essay guide.

Uni match

Uni match

Our tool will help you find the perfect course for you

Study planner

Create a study plan

Get your head around what you need to do and when with the study planner tool.

Study planner

Resources by subject

Everything from mind maps to class notes.

Hands typing

Degrees without fees

Discover more about degree-level apprenticeships.

A student doing homework

Study tips from A* students

Students who got top grades in their A-levels share their secrets

Study help links and info

Can you help? Study help unanswered threadsRules and posting guidelines

Sponsored content:

HEAR

HEAR

Find out how a Higher Education Achievement Report can help you prove your achievements.

Groups associated with this forum:

View associated groups

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

Quick reply
Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.